1991
DOI: 10.1128/mcb.11.2.803-812.1991
|View full text |Cite
|
Sign up to set email alerts
|

αB Crystallin Accumulation Is a Specific Response to Ha-ras and v-mos Oncogene Expression in Mouse NIH 3T3 Fibroblasts

Abstract: The conditional expression of the v-mos and Ha-ras(EJ) oncogenes in NIH 3T3 cells leads to the accumulation of a 23-kDa protein (p23) (R. Klemenz, S. Hoffmann, R. Jaggi, and A.-K. Werenskiold, Oncogene 4:799-803, 1989). We purified p23 to homogeneity and determined part of the amino acid sequence. The obtained sequence is identical with that of the eye lens protein alpha B crystallin. Northern (RNA) blot and Western immunoblot experiments were performed to demonstrate that alpha B crystallin mRNA and protein d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…aB-crystallin expression has been associated with a variety of pathological and experimental conditions, notably Alexander's disease (21) and Lewy body disease (31) in humans, scrapie infection in hamsters ( 14), and osmotic stress in certain cultured cells (10). In addition, it has recently been demonstrated that aB-crystallin is induced by oncogenes as well as heat shock in NIH 3T3 cells (24)(25)(26).…”
mentioning
confidence: 99%
“…aB-crystallin expression has been associated with a variety of pathological and experimental conditions, notably Alexander's disease (21) and Lewy body disease (31) in humans, scrapie infection in hamsters ( 14), and osmotic stress in certain cultured cells (10). In addition, it has recently been demonstrated that aB-crystallin is induced by oncogenes as well as heat shock in NIH 3T3 cells (24)(25)(26).…”
mentioning
confidence: 99%